Application of the Extraordinary Dictionary Through the Singing Method to Improve Arabic Vocabulary Mastery of Madrasah Diniyah Students - Solihin, Solihin (STUDI ARAB, 2025)
The primary objective of this study is to investigate the application of the Extraordinary Dictionary with a singing method to enhance Arabic mufrodat acquisition among students at Madin Ar-Rofi’iyyah. This study employs a qualitative approach. A total of 31 students from Madin Ar-Rofi’iyyah were selected as samples through a sampling technique. Data were collected through observation, interviews, and documentation. The collected information was then analyzed through data reduction, data presentation, and conclusion drawing, and further analyzed using thematic analysis. The research findings indicate that the extraordinary dictionary with the singing method proved to be an effective learning tool in improving Arabic mufrodat acquisition among students at Madin Ar-Rofi’iyyah. These findings are consistent with the research objectives and strengthen phenomenological theory. The implications of this research cover both theoretical and practical aspects. Theoretically, these results support the use of innovative methods in language learning. Practically, this research recommends that the Ar-Rofi’iyyah Islamic Boarding School Foundation adopt the extraordinary dictionary as a tool to assist students in memorizing mufrodat. Furthermore, this study opens opportunities for further research on improving students' mufrodat acquisition.